EDUKASI PENCEGAHAN DAN DETEKSI DINI KANKER SERVIKS PADA ANGGOTA PMN (PERMODALAN MEKAR MADANI) - Purbasari, Euis; Erikardo, Oktadio; Wirman, Adia Putra; Nikmatullah, Nurul Azmah; Sunaryo, Hadi; Riyanti, Hurip Budi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Cervical cancer is a malignant tumor that forms in the cervix. The primary cause of cervical cancer is an infection with oncogenic types of Human Papillomavirus (HPV), particularly types 16 and 18, which lead to abnormal growth in the cervical epithelial tissue. Other risk factors that increase the incidence of cervical cancer include sexual activity with multiple partners, sexually transmitted infections, immune disorders, having many children, low socioeconomic status, and lack of knowledge about reproductive health. The aim of this activity is to enhance participants' knowledge about reproductive organ health as well as the prevention and early detection of cervical cancer. Increasing knowledge can be achieved by providing education on the prevention and early detection of cervical cancer, as well as educating about reproductive health. The results of the educational program showed an increase in knowledge, as reflected in the improved post-test scores.